Bioaccessibility constrains the co-composting bioremediation of field aged PAH contaminated soils. (April 2020) - Leech, Calvin; Tighe, Matthew K.; Pereg, Lily; Winter, Gal; McMillan, Mary; Esmaeili, Atefeh; Wilson, Susan C.
Abstract: Co-composting for the remediation treatment of aged polycyclic aromatic hydrocarbons (PAHs) in field contaminated soil was examined in this study. Two PAH contaminated soils collected from a manufacturing gas plant site with high PAH concentrations (184.00 ± 3.99 mg kg −1 and 490.0 ± 43.53 mg kg −1 ) were co-composted with cattle manure and wheat straw for up to 56 days in laboratory microcosms. A range of optimised co-composting treatments including addition of Triton-X100 surfactant and a biological surfactant from the Australian Red Ash tree ( Alphitonia excelsa ) were tested. There was no significant decrease in the PAH concentrations in any of the different co-composting treatments for either of the soils, despite an 87% decrease in a phenanthrene spike (100 mg kg −1 ), and evidence of PAH microbial catabolic activity. Non-exhaustive extraction using hydroxypropl-β-cyclodextrin (HP-β-CD) and linear regression modelling confirmed that PAH bioaccessibility constrained PAH co-composting remediation in these soils. The results demonstrate that co-composting alone is not an effective remediation strategy for certain aged PAH contaminated soils. For these soils some form of pre-composting chemical or engineering treatment is required to overcome bioaccessibility limitations in successful remediation. Graphical abstract: Image 1 Highlights: Co-composting bioremediation was ineffective for the removal of PAHs from aged contaminated soils. Phenanthrene spiking and illumina sequencing revealed PAH microbial catabolic potential in soil. HP-β-CD extractions demonstrated low PAH bioaccessibility that limited degradation. HP-β-CD extraction shows potential for pre-screening aged soils for bioremediation.